Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To verify if [tex]\( g(x) = \frac{1}{3} x \)[/tex] is the inverse of [tex]\( f(x) = 3x \)[/tex], we need to check whether applying both functions in succession results in the original input [tex]\( x \)[/tex]. This means we need to see if [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex].
Let's break this down step-by-step for each expression:
1. [tex]\( 3x\left(\frac{x}{3}\right) \)[/tex]:
Substitute [tex]\( g(x) = \frac{1}{3} x \)[/tex] into [tex]\( f(x) = 3x \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{3} x\right) = 3 \left(\frac{1}{3} x\right) = x. \][/tex]
This is not the expression verified here but it sets the understanding.
2. [tex]\( \left(\frac{1}{3} x\right)(3x) \)[/tex]:
Substitute [tex]\( f(x) = 3x \)[/tex] into [tex]\( g(x) = \frac{1}{3} x \)[/tex]:
[tex]\[ g(f(x)) = g(3x) = \frac{1}{3} (3x) = x. \][/tex]
This confirmation looks reasonable but we move to next.
3. [tex]\( \frac{1}{3}(3 x) \)[/tex]:
Apply [tex]\( f(x) = 3x \)[/tex] first, and then [tex]\( \frac{1}{3} \)[/tex] to the result:
[tex]\[ g(f(x)) = g(3x) = \frac{1}{3}(3 x) = x. \][/tex]
[tex]\[ f(g(x)) = f\left(\frac{1}{3} x\right) = 3\left(\frac{1}{3} x\right) = x. \][/tex]
This verifies also correct.
4. [tex]\( \frac{1}{3}\left(\frac{1}{3} x\right) \)[/tex]:
Apply [tex]\( g(x) = \frac{1}{3} x \)[/tex] first, and then apply [tex]\( \frac{1}{3} \)[/tex] to [tex]\( \frac{1}{3} x \)[/tex]:
[tex]\[ g(g(x)) = g\left(\frac{1}{3} x\right) = \frac{1}{3} \left(\frac{1}{3} x\right) = \frac{1}{9} x. \][/tex]
This does not simplify to [tex]\( x \)[/tex].
Thus, the final step to choose will reveal [tex]\( \frac{1}{3}\left(3 x\right) \)[/tex] simplifies to [tex]\[ x \][/tex] making it the correct simplifier and
the applied expression:
[tex]\[ \boxed{\frac{1}{3}(3 x)} \][/tex]
which confirms [tex]\( g(x) \)[/tex] is indeed the inverse.
Let's break this down step-by-step for each expression:
1. [tex]\( 3x\left(\frac{x}{3}\right) \)[/tex]:
Substitute [tex]\( g(x) = \frac{1}{3} x \)[/tex] into [tex]\( f(x) = 3x \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{3} x\right) = 3 \left(\frac{1}{3} x\right) = x. \][/tex]
This is not the expression verified here but it sets the understanding.
2. [tex]\( \left(\frac{1}{3} x\right)(3x) \)[/tex]:
Substitute [tex]\( f(x) = 3x \)[/tex] into [tex]\( g(x) = \frac{1}{3} x \)[/tex]:
[tex]\[ g(f(x)) = g(3x) = \frac{1}{3} (3x) = x. \][/tex]
This confirmation looks reasonable but we move to next.
3. [tex]\( \frac{1}{3}(3 x) \)[/tex]:
Apply [tex]\( f(x) = 3x \)[/tex] first, and then [tex]\( \frac{1}{3} \)[/tex] to the result:
[tex]\[ g(f(x)) = g(3x) = \frac{1}{3}(3 x) = x. \][/tex]
[tex]\[ f(g(x)) = f\left(\frac{1}{3} x\right) = 3\left(\frac{1}{3} x\right) = x. \][/tex]
This verifies also correct.
4. [tex]\( \frac{1}{3}\left(\frac{1}{3} x\right) \)[/tex]:
Apply [tex]\( g(x) = \frac{1}{3} x \)[/tex] first, and then apply [tex]\( \frac{1}{3} \)[/tex] to [tex]\( \frac{1}{3} x \)[/tex]:
[tex]\[ g(g(x)) = g\left(\frac{1}{3} x\right) = \frac{1}{3} \left(\frac{1}{3} x\right) = \frac{1}{9} x. \][/tex]
This does not simplify to [tex]\( x \)[/tex].
Thus, the final step to choose will reveal [tex]\( \frac{1}{3}\left(3 x\right) \)[/tex] simplifies to [tex]\[ x \][/tex] making it the correct simplifier and
the applied expression:
[tex]\[ \boxed{\frac{1}{3}(3 x)} \][/tex]
which confirms [tex]\( g(x) \)[/tex] is indeed the inverse.
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.